THE VALIDITY FOR THE APPLICATION OF SOLAR ENERGY IN IRRIGATION OF PERENNIAL PLANTS IN FRUIT GROWING IN THE REPUBLIC OF SERBIA - Aleksandar Ašonja; Jasmina Pekez; Nenad Janjić; Danilo Mikić (Applied Engineering Letters, 2016)
Constant increase in the number of people in the world today imposes the need for constant increase in food yield on the one side and energy on the other. The presented survey compiles two technological processes that use solar energy for their functioning. These are solar panels that produce electricity and agricultural production (seen through the irrigation process) which develops herbal mass (weight) by the means of photosynthesis. The aim of the research was to investigate the validity of applying solar energy in irrigation of perennial plants in fruit growing in the Republic of Serbia. This paper will explore the energy obtained from solar panels for irrigation purposes for the period (April-October) in which the requirements of plants for water are the highest. The justification for the application of solar energy in irrigation of perennial plants is compared, with the prices of diesel fuel and electricity from the network.